Analisis Kadar Asam Lemak Bebas dan Colour untuk Pengendalian Mutu Minyak Goreng di PT.X - Widya, Widya Fernanda Putri; Tarigan, Sri Wahyuni; Fadly, Fadly (Fakultas Teknologi dan Ilmu Komputer, Universitas Prima Indonesia, 2023)
Palm oil used as a food product is usually produced from palm oil as well as from palm kernel oil through fractionation, refinement and hydrogenation. PT.X produces the main product, namely cooking oil (olein). The cooking oil in the manufacturing process comes from CPO (Crude Palm Oil) which undergoes a degumming, bleaching, filtration process using a Niagara filter and deodorization at the Refining Plant with the resulting product being RBDPO (Refined, Bleached, and Deodorized Palm Oil). This research aims to determine the levels Free Fatty Acids (ALB) in CPO and RPO as well as knowing the color levels in CPO and RPO according to standards at PT. X. From the results of the analysis carried out in the PT. The free fatty acid content in crude palm oil (CPO) and refined palm oil (RPO) obtained an average value of 3.29% and 0.042%. Meanwhile, the color content results for crude palm oil (CPO) and refined palm oil (RPO) obtained an average of 22R and 1.7R. Based on the results of analysis of free fatty acids (ALB) and color in crude palm oil (CPO) and refined palm oil (RPO) in the PT. Key words: palm oil, free fatty acids, color, CPO, and RPO.